2007
DOI: 10.1111/j.1462-2920.2007.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing diversity and biogeography of aerobic anoxygenic phototrophic bacteria in surface waters of the Atlantic and Pacific Oceans using the Global Ocean Sampling expedition metagenomes

Abstract: Aerobic anoxygenic photosynthetic bacteria (AAnP) were recently proposed to be significant contributors to global oceanic carbon and energy cycles. However, AAnP abundance, spatial distribution, diversity and potential ecological importance remain poorly understood. Here we present metagenomic data from the Global Ocean Sampling expedition indicating that AAnP diversity and abundance vary in different oceanic regions. Furthermore, we show for the first time that the composition of AAnP assemblages change betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
250
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(273 citation statements)
references
References 43 publications
(84 reference statements)
21
250
1
1
Order By: Relevance
“…The GOS project produced a total of 7.7 million random sequence reads, yielding approximately 6.3 Gb of assembled environmental DNA sequences from such diverse environments as the North Atlantic Ocean, the Panama Canal and the South Pacific Gyre . This data set was already mined for the presence of anoxygenic photosynthesis genes ('non-cyanobacterial') in search for diversity and biogeography of anoxygenic phototrophic bacteria (Yutin et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The GOS project produced a total of 7.7 million random sequence reads, yielding approximately 6.3 Gb of assembled environmental DNA sequences from such diverse environments as the North Atlantic Ocean, the Panama Canal and the South Pacific Gyre . This data set was already mined for the presence of anoxygenic photosynthesis genes ('non-cyanobacterial') in search for diversity and biogeography of anoxygenic phototrophic bacteria (Yutin et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, various reports showed that these organisms are abundant in eutrophic as well as in oligotrophic environments (Jiao et al, 2007;Koblížek et al, 2006;Yutin et al, 2007). Other authors suggested that nutrient concentrations (Mašín et al, 2008), attachment to particles Waidner and Kirchman, 2007) or light intensity (Koblížek et al, 2003;Shiba, 1991) may influence AAP bacterial abundance.…”
mentioning
confidence: 95%
“…Kolber et al (2000) suggested that AAP bacteria might be abundant in oligotrophic oceanic regions where the capacity to harvest light energy may provide photoheterotrophs a competitive advantage over chemoheterotrophs. Later studies showed that their abundance and distribution vary greatly among oceanic regimes, suggesting that there is a broad range of potential ecological niches for these microbes (Cottrell et al, 2006;Lehours et al, 2010;Mašín et al, 2006;Sieracki et al, 2006;Yutin et al, 2007). It seems however that AAP bacteria are more abundant in shelf and coastal areas than in the open ocean (Schwalbach and Fuhrman, 2005;Sieracki et al, 2006).…”
Section: Aerobic Anoxygenic Phototrophic Bacteriamentioning
confidence: 99%